2019
DOI: 10.1186/s12871-019-0812-9
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management of tracheal laceration from traumatic dislocation of the first rib: a case report and literature of the review

Abstract: Background Tracheobronchial lacerations from trauma can be life-threatening and present significant challenges for safe anesthetic management. Early recognition of tracheal injuries and prompt airway control can be lifesaving. Case presentation A 56-year-old man with no significant medical history presented with difficulty breathing after a blunt trauma to his chest to the emergency room and was diagnosed with dislocation of the first rib and tracheal laceration after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…In some cases, awake intubation may be safe, and if patient cooperation is difficult, it may be safe to perform induction while maintaining spontaneous ventilation. If intubation fails, tracheostomy and ECMO/CPB should be considered [13]. Tracheostomy may also be required to prevent the expansion of subcutaneous emphysema, bypass the tear site, and prevent further complications [14].…”
Section: Case Reportmentioning
confidence: 99%
“…In some cases, awake intubation may be safe, and if patient cooperation is difficult, it may be safe to perform induction while maintaining spontaneous ventilation. If intubation fails, tracheostomy and ECMO/CPB should be considered [13]. Tracheostomy may also be required to prevent the expansion of subcutaneous emphysema, bypass the tear site, and prevent further complications [14].…”
Section: Case Reportmentioning
confidence: 99%
“…While cervical tracheal injuries infrequently occur, it has been reported that about 75% of victims immediately died due to respiratory failure, airway obstruction, or tension pneumothorax or head injury [Zhao 2017;Eduardo 2009;Weil 2019]. Also, late complications were reported, such as tracheal stenosis or repeated chest infections.…”
Section: Introductionmentioning
confidence: 99%